Network Intelligence as a Necessity of the New Time - Viktorovich, Tolstoguzov Oleg; Dmitrievna, Belykh Anastasia (International Journal of Emerging Trends in Social Sciences, 2021)
Realization of a modernization agenda requires improvement of competencies and intellectualization of territorial development of the management system in conditions of increasing uncertainty of the management situation and systemic risks. The purpose of our study was to analyze a spatial distribution of an intellectual potential of regions and propose a conclusion about leveling of risks from gaps in the economic space. We consider the following competencies as a basis of a potential that determines intellectualization of the management system. This is the ability to train personnel of HSQ and create and promote innovations. The factor analysis was used as a tool. The following conclusion was made: it is necessary to pay attention to development of national scientific schools because the education system is a basis for a formation of the competence economy. Moreover, it is necessary to stimulate development of the entire system of knowledge reproduction, and the entire space without gaps. The pandemic forced active development of digital platforms, transferring many spheres of public life. Opportunities for creating “the network intelligence” have increased. The need to improve competencies has increased, including development of a digital environment. It is possible to eliminate systemic risks that have arisen due to the gap in the economic space by strengthening collaborations based on digital platforms and forming “the network intelligence”. The basic element of knowledge reproduction is training of qualified personnel at the university education system. Therefore, it is necessary to continue strengthening the integration and form collective models of the innovation process.